Bacteriological study and antibiogram of urinary tract infection in children from a tertiary care hospital - Pathya, Diksha; Tripathi, Gaurav (International Journal of Contemporary Pediatrics, 2026)
Background: The purpose of this observational study was to evaluate the aetiology and antimicrobial resistance pattern in urinary tract infection among children under 18 years of age. Methods: It was a retrospective observational study carried out in Sanjay Gandhi memorial hospital, Rewa over a period of 18 months from March 2023 to August 2024. The study included 362 children below 18 years of age whose urine cultures were positive for the growth of an organism. Their demographic characteristics, aetiological agents and antimicrobial resistance were evaluated. Results: Among the 362 patients UTI was more common among females (54.15%). In age group of 0-1 years of age UTI was more in males as compared to females. Most common isolated organism was E. coli (n=105, 29.05%). In our study gram negative uropathogens showed highest sensitivity to imipenem followed by gentamycin whereas gram positive uropathogens showed highest sensitivity to tetracycline followed by chloramphenicol. Conclusions: Our study found that Escherichia coli continues to be a predominant cause of urinary tract infections in children. However, there has been a notable shift in antibiotic susceptibility, with many frequently prescribed medications now exhibiting significant resistance. Therefore, it is important to have institute based antibiogram for prompt treatment of UTI and limiting of further antibiotic resistance.